Peningkatan pengetahuan “Pentingnya Perilaku Hidup Bersih dan Sehat” pada Posyandu Remaja Mojo Gubeng Surabaya - Purbowati, Rini; Soekanto, Ayly; Rahmawati, Febtarini; Tjandra, Lusiani; Masfufatun; Devi Dwi Rianti, Emilia; Kumala Indahsari, Noer (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Indonesia is currently facing a double burden of diseases, namely Communicable Diseases (PM) and Non-Communicable Diseases (NCD) which are strongly influenced by changes in the environment, community behavior, demographic transition, technology, economy, and socio-culture. To overcome this problem, the government has intensified the Program Perilaku Hidup Bersih dan Sehat (PHBS), which should involve all elements of society, stakeholders, the private sector, academia, and non-governmental organization (NGOs) and other sectors. The role of young people is needed by the government in the process of sustainable development or the Sustainable Development Goals (SDGs). The purpose of this activity is to increase public knowledge and awareness, especially among members of the Youth Posyandu Mojo Gubeng Surabaya about the importance of clean and healthy living behavior. This service activity was carried out on Saturday 11 September 2021, attended by 26 participants. This community service activity was chosen in the form of an online seminar (webinar) to support the government in handling COVID-19 by implementing Emergency PPKM. Measurement of the increase in participants' knowledge was carried out through pre-test and post-test by answering questions related to the webinar material by filling out Google Forms. The measurement results obtained a pre-test average and post-test average value (82.1±18) with a delta value (change in score) of 18.6. Community Service Activities through a Webinar with the title